Phosphoric acid modified charcoal adsorbent preparation method and product and application thereof
By pretreating cotton straw NaOH and modifying H3PO4, phosphoric acid modified biochar adsorbent (PCS) was prepared, which solved the problem of difficulty in effectively removing hexavalent chromium in water in the prior art, and achieved a significant improvement in the removal efficiency of Cr(VI).
Patent Information
- Application Number
- CN202411734033.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively remove hexavalent chromium (Cr(VI)) in water, while biochar modification technology is relatively limited in related research.
After NaOH pretreatment of cotton straw, it is mixed with H3PO4 solution, and calcined at high temperature and HCl treatment, a phosphoric acid modified biochar adsorbent (PCS) is prepared.
PCS significantly improved the removal efficiency of Cr(VI), reaching an equilibrium adsorption amount of 61.7 mg g-1, exceeding the removal capacity of unmodified biochar and potassium carbonate modified biochar.
Smart Images

Figure CN119793394A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of environmental functional materials and biomass resource utilization, and specifically relates to a method for preparing a phosphoric acid-modified biochar adsorbent, a product thereof and an application thereof. Background Art
[0002] The continuous emission of toxic elements (TEs) into aquatic environments from industrial activities such as metal smelting, steel manufacturing, and dye production is considered a critical environmental issue. Among TEs, chromium (Cr) has attracted worldwide attention due to its highly carcinogenic, genotoxic, and easily mobile nature, posing a serious threat to human and ecological health through bioaccumulation. Given that Cr(VI) is about 1,000 times more toxic than Cr(III), making it a major target for remediation efforts, the most promising approaches to eliminate Cr(VI) include adsorption and reduction processes. Therefore, effective technologies must be advanced to adsorb and reduce Cr(VI) in order to protect water quality and human health.
[0003] In recent years, researchers have found that nanomaterials such as biochar and zero-valent iron have significant adsorption capacity and effective reduction properties for various pollutants. Biochar, a waste biomass-derived carbon material, has become a widely used solution for remediation of chromium-contaminated soil and water due to its excellent performance and cost-effectiveness. Cr species are immobilized by interacting with abundant active sites on biochar. To improve the removal efficiency of chromium, biochar has been physically, chemically, and biologically modified to enhance properties such as surface area and functional groups. It has been found that H3PO4 activation of eucalyptus biochar improves the pore structure and increases CO and C-OH groups. These modifications promote the effective elimination of Cr(VI) through physical adsorption and chemical reduction. Preparation of biochar containing O and P functional groups by pyrolysis of H3PO4-modified biomass can improve the removal efficiency of Cr(VI), but related research is very limited. Summary of the invention
[0004] In order to solve at least one of the above problems, the present invention provides a method for preparing a phosphoric acid-modified biochar adsorbent, and its product and application, especially its application in removing Cr(VI).
[0005] On the one hand, the present invention provides a method for preparing a phosphoric acid-modified biochar adsorbent:
[0006] (1) Take cotton stalks, dry them, grind them and sieve them;
[0007] (2) The cotton stalks treated in step (1) were immersed in a NaOH solution, placed in a high-temperature sterilizer, washed with ultrapure water, and dried to obtain a product named CS NaOH ;
[0008] (3) Take CS NaOHMixing with H3PO4 solution, impregnating, and drying to obtain a mixture;
[0009] (4) placing the mixture of step (3) in a tube furnace in a N2 environment, calcining at high temperature, and then cooling naturally to obtain a black solid;
[0010] (5) The black solid obtained in step (4) was mixed with HCl solution and shaken, then washed with ultrapure water and anhydrous ethanol, and dried to obtain a phosphoric acid-modified biochar adsorbent named PCS.
[0011] Furthermore, in the step (1), pre-cleaning is performed, the drying temperature is 105° C., and the sieving mesh number is 100 meshes.
[0012] Furthermore, in step (2), the concentration of the NaOH solution is 1.000M.
[0013] Furthermore, in step (3), the concentration of the H3PO4 solution is 8.093M.
[0014] Furthermore, in the step (4), the calcination temperature in the tubular furnace is 500°C.
[0015] Furthermore, in step (2), 10 g of cotton straw is added to every 1 L of 1 M NaOH solution.
[0016] Furthermore, in step (3), 9.036 mL of 8.093 M H3PO4 solution was added with 3.600 g CS NaOH .
[0017] Furthermore, in step (4), the concentration of the HCl solution is 1M, and the concentration of the formed solid is 10 g / L -1 .
[0018] A second aspect of the present invention provides a phosphoric acid-modified biochar adsorbent prepared by the above method.
[0019] A third aspect of the present invention provides an application of a phosphoric acid-modified biochar adsorbent, specifically for adsorbing and removing hexavalent chromium.
[0020] Beneficial effects of the present invention:
[0021] (1) The raw materials of the phosphoric acid-modified biochar adsorbent prepared by the method of the present invention are low-cost, easy to obtain, pollution-free, can be prepared on a large scale, and have controllable structure and performance, and have broad application prospects.
[0022] (2) The phosphoric acid-modified biochar adsorbent prepared by the method of the present invention has the functions of both adsorbing and reducing Cr(VI).
[0023] (3) Adsorption experiments have shown that the phosphoric acid-modified biochar adsorbent provided by the present invention can more effectively remove Cr(VI) than unmodified biochar material (CS) and potassium carbonate-modified biochar material (KCS). PCS reaches equilibrium in about 4 hours and shows the highest equilibrium adsorption capacity of 61.7 mg g -1 , exceeding CS (14.2 mg g -1 ) and KCS (35.7 mg g -l ). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Prepare flow chart for PCS;
[0025] Figure 2 SEM images of CS, PCS and KCS;
[0026] Figure 3 is the SEM-EDS image of PCS;
[0027] Figure 4 This is the SEM-EDS image of PCS after adsorption of Cr(VI);
[0028] Figure 5 FTIR graphs of CS, PCS and KCS;
[0029] Figure 6 XPS graphs of CS, PCS and KCS;
[0030] Figure 7 is the adsorption capacity diagram of CS, PCS and KCS for Cr(VI) at the initial solution pH;
[0031] Figure 8 The adsorption kinetics of CS, PCS and KCS;
[0032] Fig. 9 It is the intra-particle diffusion diagram of CS, PCS and KCS;
[0033] Fig.10 is the adsorption isotherm diagram of CS, PCS and KCS;
[0034] Fig.11 The adsorption isotherms of CS, PCS and KCS at different temperatures. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification. The methods described are all conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.
[0036] The term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] The present invention provides a method for preparing a phosphoric acid-modified biochar adsorbent:
[0038] The specific preparation steps are:
[0039] (1) Take cotton stalks, dry them, grind them and sieve them;
[0040] (2) The cotton stalks treated in step (1) were immersed in a NaOH solution, placed in a high-temperature sterilizer, washed with ultrapure water, and dried to obtain a product named CS NaOH Alkaline pretreatment can reduce lignin and cellulose in straw, expand the microfiber gap in straw, cause changes in straw structure, and change the elemental composition, functional groups, surface positive and negative charges and specific surface area of straw, thereby changing the adsorption capacity of biochar for organic pollutants and heavy metals. This study used NaOH to moderately pretreat the lignocellulose structure of crop straw and enhance the impregnation of phosphate and potassium carbonate.
[0041] (3) Take CS NaOH Mixing with H3PO4 solution, impregnating, and drying to obtain a mixture;
[0042] (4) placing the mixture of step (3) in a tube furnace in a N2 environment, calcining at high temperature, and then cooling naturally to obtain a black solid;
[0043] (5) The black solid obtained in step (4) was mixed with HCl solution and shaken, then washed with ultrapure water and anhydrous ethanol, and dried to obtain a phosphoric acid-modified biochar adsorbent named PCS.
[0044] Example 1
[0045] refer to Figure 1 Flowchart in
[0046] (1) Clean cotton straw powder is washed to remove dust, dried at 105°C, ground and passed through a 100-mesh sieve.
[0047] (2) 10 g of cotton straw was immersed in 1 L of 1.000 M NaOH solution, ultrasonicated for 10 min, and shaken for 30 min. The solution was placed in a high temperature sterilizer and treated at 121 °C and 15 psi for 30 min. The product was washed with ultrapure water several times and dried at 105 °C for 12 h. It was named CS. NaOH .
[0048] (3) Take 3.600g CS NaOH , mixed with 9.036 mL 8.093 M H3PO4 solution, ultrasonicated for 10 min, shaken for 12 h, and dried at 80 °C for 12 h.
[0049] (4) The mixture of step (3) was placed in a tube furnace in a N2 environment at 10°C min -1 Raise the temperature to 500°C, maintain for 2 hours, and allow to cool naturally.
[0050] (5) The black solid from step (4) was mixed with 1M HCl solution (solid concentration of 10 g L -1 ), mixed and shaken for 30 min to remove ash, then washed with ultrapure water and anhydrous ethanol, dried at 105 °C for 12 h, and named PCS.
[0051] Comparative Example 1
[0052] Take the cotton stalks treated in step 1 of Example 1 and heat them at 10°C min -1 Heated to 500℃, named CS
[0053] Comparative Example 2
[0054] Take 4.146 g CS prepared in step 2 of Example 1 NaOH Mix with 30 mL of 2M K2CO3 solution, shake vigorously at room temperature for 4 h, dry at 105 °C to constant weight, place in a tube furnace in a N2 environment and heat at 10 °C min -1 The temperature was raised to 500 °C and maintained for 2 h, and the pickling, washing and drying steps were the same as above, and it was named KCS.
[0055] The PCS, CS and KCS prepared in Example 1 and Comparative Examples 1 and 2 were tested. Figures 2 to 4 The morphology of CS, PCS, and KCS as well as the adsorption of Cr(VI) on PCS was examined using SEM and EDS images as shown in Figure 2. A fairly smooth structure was observed on the surface of CS, while the surfaces of PCS and KCS were characterized by a more developed wrinkled morphology and pore structure ( Figure 2 ). SEM-EDS images show that PCS contains uniformly distributed C, O, N and P elements ( Figure 3 ), indicating the successful doping of P element, which may promote the chemical adsorption of Cr(VI) by introducing phosphorus into the surface functional groups. Figure 4 In the experiment, Cr adsorption was found on the PCS surface.
[0056] Figure 5 The FT-IR spectra of CS, PCS and KCS are shown. 3434, 1626, 1382 and 1026 cm-1 The peaks at 1160 and 1026 cm reveal the presence of hydrogen-bonded OH, C=O, C-OH, and COC functional groups on the biochar surface. After modification with H3PO4 or K2CO3, the peaks associated with C=O, C-OH, and COC become significantly stronger. In particular, the peaks at 1160 and 1026 cm -1 The new peaks at are related to CP and PO vibrations, indicating that phosphorus is attached through interactions with surface functional groups such as hydroxyl, ether, and hydride. XPS spectroscopy was used to further understand the elemental composition of biochar and the measured spectra, such as Figure 6 .exist Figure 6 In b, in the C1s XPS spectrum, three main peaks were observed at 248.80, 285.70, and 288.20 eV, corresponding to C=C / CC, COC / C-OH, and C=O / CP, respectively. The relative content of COC / C-OH in PCS is lower than that in CS, which may be due to the higher content of C=O / CP in PCS. Figure 6 c, the O 1s spectrum shows peaks at 531.50, 532.30, 533.60, and 535.60 eV, corresponding to C=O, OC=O, COC / C-COH, and adsorbed H2O, respectively. H3PO4 modification increases the carboxyl content from 31.3% to 42.9%, and K2CO3 modification increases the hydroxyl content from 32.3% to 38.7%. The P 2p spectrum of PCS shows four peaks at 133.20, 134.25, 135.15, and 136.80 eV, corresponding to C3-PO, CPO, COP, and P=O, respectively, while CS contains only the peak corresponding to C3-PO ( Figure 6 d). It is noteworthy that PCS contains a large amount of CPO groups (46.3%), which have been shown to have high stability and reduction activity in previous studies. Therefore, compared with CS, PCS and KCS exhibit larger functional groups (i.e., -COOH, CPO groups), providing more adsorption sites for Cr(VI), which is consistent with the FT-IR results.
[0057] The adsorption kinetics were studied to determine the equilibrium time and to reveal the adsorption mechanism, including mass transfer and diffusion controlled processes. Figure 8 As shown in Figure 2, CS, PCS, and KCS rapidly adsorbed Cr(VI) within the first 2 h, reaching 77.2%, 93.6%, and 83.3% of the equilibrium adsorption, respectively. Then, the adsorption rate decreased and reached equilibrium in about 4 h. PCS showed the highest equilibrium adsorption capacity of 61.7 mg g -1 , exceeding CS (14.2 mg g -1 ) and KCS (35.7 mg g -lThe adsorption kinetics data were modeled by PFO, PSO, AFO and Elovich models ( Figure 4 ). The adsorption of Cr(VI) by CS, PCS and KCS is consistent with the above four kinetic models. The Elovich model has the highest correlation coefficient (R2>0.99). The equilibrium adsorption capacity obtained by PSO model fitting is closer to the experimental results, indicating that the adsorption of Cr(VI) by these adsorbents may involve physical and chemical reactions. Fig. 9 As shown in Figure 2, further simulations of the IPD model showed that the adsorption process can be divided into two steps: boundary layer diffusion and intraparticle diffusion. The boundary layer effect index C of PCS is 5.0 mg L -1 , which is equivalent to 8.1% of the equilibrium adsorption, indicating that the intraparticle diffusion mainly controls the adsorption process of Cr(VI).
[0058] Adsorption isotherms were performed to investigate the adsorption capacity of the adsorbents and to gain insight into the interaction with Cr(VI). Fig.10 As shown in Figure 2, the adsorption capacity of the three adsorbents increased with the increase of Cr(VI) concentration until equilibrium was reached. The adsorption process of CS, PCS and KCS was similar to that of Langmuir (R 2 >0.98) and Sips LF(R 2 >0.99) model, indicating that the monolayer adsorption has uniform surface adsorption sites. The Langmuir model accurately predicted the adsorption capacities of CS, PCS, and KCS to be 35.5, 138.9, and 67.3 mg g, respectively. -1 , which is in good agreement with the experimental data at 298 K. As the temperature increases from 298 K to 318 K, the maximum adsorption capacity of PCS increases from 138.9 mg g -1 Reduced to 95.5 mg g -1 ( Fig.11 ).
[0059] The method for investigating the adsorption performance of simulated pollutants provided by the present invention is as follows:
[0060] Adsorption test:
[0061] In a 100 mL blue cap bottle, use 0.5 g L -1 Biochar in 50 mL 50 mg L -1 The adsorption experiment of Cr(VI) was carried out in Cr(VI) solution. -1HCl and NaOH were used to adjust the pH of the solution. The mixture was shaken in the dark at 25 °C and 150 rpm for 240 min. 0.5 mL of the collected liquid samples were filtered regularly using a 0.22 μm filter, and the Cr(VI) concentration was determined. In addition, the effects of initial pH (3.0-11.0) and temperature (298-318 K) on the adsorption of Cr(VI) by biochar were studied, and all experiments were performed in triplicate.
[0062]
[0063] η refers to the removal rate, which is the ratio of the amount of Cr(VI) after adsorption to that before adsorption, Q e (mg·g -1 ) is the Cr(VI) adsorption capacity of the adsorbent at the equilibrium time, C e (mg·L -1 ) is the concentration of Cr(VI) in the aqueous phase at equilibrium, C0 (mg·L -1 ) is the concentration of Cr(VI) in the solution before adsorption.
[0064] The initial pH of the aqueous solution significantly affects the surface charge characteristics of the Cr(VI) species and the adsorbent. Figure 7 The uptake of Cr(VI) by CS, PCS, and KCS was confirmed to be pH-dependent. For example, at pH 3.0, PCS showed an uptake of 61.7 mg g -1 However, as the pH value increased to 8.0, the removal capacity dropped sharply to 20.7 mg g -1 , maintained at 20.7 to 18.7 mg g in the pH range of 8.0 to 11.0 -1 Typically, Cr(VI) is present as HCrO4 at pH < 6.0. - and Cr2O7 2- It exists in the form of CrO4 when pH>7.0 2- The pH of PCS PZC The pH value of the zero charge point was determined to be 2.5. <pH PZC When the functional groups (such as -OH, -COOH) on PCS are protonated, the positively charged surface enhances the electrostatic adsorption of HCrO4 - and Cr2O7 2- On the contrary, when pH>pH PZC The deprotonation of the functional groups leads to a decrease in the positive charge on the PCS surface, thereby inhibiting the adsorption of anionic Cr(VI).
[0065] Detection method:
[0066] In the experiments, the Cr(VI) concentrations of all samples were measured using a UV-vis spectrometer (UV2700, Japan) at a wavelength of 540 nm.
[0067] Then five well-recognized kinetic models, namely, pseudo-first-order (PFO), pseudo-second-order (PSO), Avrami fractional (AFO), Elovich, and intraparticle diffusion (IPD) models, were selected to fit the kinetic data of Cr(VI) removal.
[0068]
[0069] Q e and Q t (mg g -1 ) are the amount of Cr(VI) adsorbed by the adsorbent at equilibrium time and time t; k1(min -1 )、k2(mg(g min) -1 ) and k Av (min -1 ) are pseudo-first-order, pseudo-second-order and Avrami kinetic constants; n Av is the Avrami exponential constant (dimensionless). α(mg(g min) -1 ) and β(g min -1 ) are the kinetic constants (dimensionless), pseudo-secondary and Avrami kinetic constants of adsorption; nAv is the Avrami exponential constant (dimensionless). α (mg (g·min)-1) and β (g·min-1) are the Elovich constants. k i (mg g -1 min -1 / 2 ) is the intraparticle diffusion modeling constant; C is related to the adsorbent thickness and boundary layer.
[0070] The adsorption data were then analyzed using three well-known isotherm models, namely, Langmuir, Freundlich, and Sips Langmuir-Frendlich (Sips LF) models, to predict heterogeneous adsorption.
[0071]
[0072] Among them C e (mg·g -1 ) is the concentration of Cr(VI) in the aqueous phase at equilibrium; Q max (mg·g -1 ) and K L (L·mg -1 ) are Langmuir model constants, representing the maximum adsorption capacity and adsorption affinity between the adsorbent and the adsorbate, respectively; K F (μ·g1 -1 / n ·L 1 / n ·g -1 )and n F is the Freundlich model constant; K S (L·mg -1 )and n S is the Sips LF model constant.
[0073] Thermodynamic model, namely Gibbs Helm Holtz equation, is used to understand the Cr 6+ Thermodynamics of adsorption to illustrate the spontaneity of the adsorption process.
[0074] ΔG 0 =RTlnK d
[0075] ΔG 0 =ΔH 0 -TΔS 0
[0076]
[0077] ΔG 0 (kJ mol -1 ) is the standard Gibbs free energy, ΔH 0 (kJ mol -1 ) is the enthalpy change, ΔS 0 (kJ mol -1 K -1 ) is the entropy change, K d (L mol -1 ), K d (L mol -1 ) is the adsorption equilibrium constant, R is the gas constant (8.314 J mol -1 K -1 ), T is the temperature in Kelvin.
[0078] The above are only several preferred embodiments of the present invention. Any modifications or changes made by technicians familiar with this field according to the spirit and scope of the present invention should be included in the scope of the technical solution of the present invention.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a phosphoric acid-modified biochar adsorbent, characterized in that: Specifically (1) Take cotton stalks, dry them, grind them and sieve them; (2) The cotton stalks treated in step (1) were immersed in a NaOH solution, placed in a high-temperature sterilizer, washed with ultrapure water, and dried to obtain a product named CS NaOH ; (3) Take CS NaOH Mixing with H3PO4 solution, impregnating, and drying to obtain a mixture; (4) placing the mixture of step (3) in a tube furnace in a N2 environment, calcining at high temperature, and then cooling naturally to obtain a black solid; (5) The black solid obtained in step (4) was mixed with HCl solution and shaken, then washed with ultrapure water and anhydrous ethanol, and dried to obtain a phosphoric acid-modified biochar adsorbent named PCS.
2. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 1, characterized in that: In the step (1), pre-cleaning is performed, the drying temperature is 105° C., and the sieve mesh number is 100 meshes.
3. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 1, characterized in that: In the step (2), the concentration of the NaOH solution is 1.000M.
4. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 1, characterized in that: In the step (3), the concentration of the H3PO4 solution is 8.093M.
5. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 1, characterized in that: In the step (4), the calcination temperature in the tubular furnace is 500°C.
6. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 3, characterized in that: In the step (2), 10 g of cotton straw is added to every 1 L of 1 M NaOH solution.
7. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 4, characterized in that: In step (3), 9.036 mL of 8.093 M H3PO4 solution was added to 3.600 g CS NaOH .
8. The method for preparing the phosphoric acid-modified biochar adsorbent according to claim 2, characterized in that: In step (4), the concentration of the HCl solution is 1M, and the concentration of the formed solid is 10 g L -1 .
9. A phosphoric acid-modified biochar adsorbent, characterized in that: The method is prepared by any one of claims 1 to 8.
10. An application of a phosphoric acid-modified biochar adsorbent, characterized in that: Used for removal of hexavalent chromium by adsorption.
Citation Information
Patent Citations
Preparation method of porous biological carbon heavy metal adsorbing material based on cotton straw
CN104941589A
Preparation method of enteromorpha biochar modified by phosphoric acid and application of enteromorpha biochar for removal of heavy metal cadmium
CN110681350A
Phosphoric acid modified peanut shell biochar material as well as preparation method and application thereof
CN111346603A
Preparation method of phosphoric acid activated eucalyptus charcoal adsorbent and application thereof in adsorbing Cr (VI) in water
CN112619606A
Aerogel adsorbent for efficiently removing cadmium as well as preparation method and application of aerogel adsorbent
CN119034691A